Estudo ontogênico e taxonômico das larvas de algumas espécies de peixes da região Norte do Brasil - ANUNCIAÇÃO, Erica Moema Silva da (Universidade Federal do Pará, 2013)
This study aimed to provide information on the morphological description of the species and ontogenetic Plagioscion squamosissimus (Sciaenidae), Cynoscion acoupa (Sciaenidae), Colomesus pscitacus (Tetraodontidae) and Oligoplites palometa (Carangidae) from the northern region of Brazil. All individuals were analyzed for the integrity of their structures and subsequently identified. From the identification of each species, individuals were analyzed for their morphological, meristic, morphometric. To study the ontogenic were determined inflection points in the growth of structures, the development stages and their critical periods, then a PCA was performed for better visualization of the characters that best define the larval growth. The results indicated that the relative growth (depending on total length (TL) of the body parts studied followed negative allometry. The three stages of larval development defined depending on the ontogenic process differed between species in spite of their similarities in the chronology of the development body. So the initial development phase of the four species in F1 favors the anterior portion of the larvae while the back of the body showed the highest growth rate at the end of the larval stage. The two species of Sciaenidae Cynoscion acoupa and Plagioscion squamosissimus differ in the shape of the mouth and CT were observed when the first teeth, the differences also in the sequence of development of the fins, pigmentation in the presence and location of spines and body proportions. Colomesus pscitacus observed the occurrence of ossified teeth soon after hatching, this species occurs also the early appearance of the fins, pigmentation and maintaining body relation (characterizing the spherical shape of the body). Oligoplites palometa The species showed the pattern of development of the fins similar to those described for other species of this family which is associated as a standard characteristic for this family, as well as the presence of intense pigmentation and spines on opercular region and supra-occipital.